2018
DOI: 10.5195/ijt.2018.6268
|View full text |Cite
|
Sign up to set email alerts
|

The Provider’s Experience of Delivering an Education-based Wellness Program via Telehealth

Abstract: Provider acceptance is a first step to implementing a successful telehealth program. This pilot study examined the experience of six providers delivering an education-based wellness program in a telehealth format. Providers indicated an overall positive experience with high Telehealth Usability Questionnaire (TUQ) total scores (5.6 ± 1.1) and in their comments. High TUQ subscale scores for Usefulness (6.7 ± 0.4) and Ease of Use (5.3 ± 0.3) indicated providers found the telehealth system usable. Strong relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 21 publications
1
24
0
Order By: Relevance
“…Factors that increase provider acceptance include a good relationship with an information technology team, a video aspect to technology, younger provider age, more recent medical training, and previous experience with telehealth. 22 These findings suggest 2 large areas of improvement. First, telehealth should be introduced to medical students and residents early in their career.…”
Section: Provider Barriersmentioning
confidence: 92%
“…Factors that increase provider acceptance include a good relationship with an information technology team, a video aspect to technology, younger provider age, more recent medical training, and previous experience with telehealth. 22 These findings suggest 2 large areas of improvement. First, telehealth should be introduced to medical students and residents early in their career.…”
Section: Provider Barriersmentioning
confidence: 92%
“…Telehealth survey instruments have primarily been used to assess patient J o u r n a l P r e -p r o o f experience (n=41, 91%) 23,24, with less frequent use to assess family caregiver (n=7, 16%) 28, 34,37,40,65,66 or medical provider experience (n=8, 18%). 23,35,40,[67][68][69][70][71] Telehealth surveys have been under-utilized to assess the experience of pediatric or adolescent cohorts with only two (4%) surveys used to assess the experience of pediatric care experiences or pediatric family caregiver experiences: TeSS for use in pediatric surgery telehealth communication 72 and TAM for pediatric telehospice care. 26 Fifteen studies (33%) included geriatric participants.…”
Section: Previous Populationsmentioning
confidence: 99%
“…The key to the implementation of a successful telehealth program is the provider s acceptance (Serwe, 2018). Providers tend to view telehealth less positively and have more concerns than the clients (Serwe, 2018).…”
Section: Statement Of Problemmentioning
confidence: 99%
“…The key to the implementation of a successful telehealth program is the provider s acceptance (Serwe, 2018). Providers tend to view telehealth less positively and have more concerns than the clients (Serwe, 2018). Dunkley, Pattie, Wilson, and McAllister (2010) found that due to the inherent technical difficulties that come with the use of technology, these difficulties have a chance to outweigh the potential benefits of the program.…”
Section: Statement Of Problemmentioning
confidence: 99%
See 1 more Smart Citation